Sweet bread products: compliance with the portuguese Integrated Strategy for the Promotion of Healthy Eating (EIPAS) - Rodrigues, H.I. (2021)
Introduction: Sweet breads are products widely consumed in Portugal. Being foods rich in fats and salt, their high consumption can compromise a healthy diet, leading to an increase in chronic non-communicable diseases. There are several health promoting strategies that aim to reduce the content of these components to contribute to an improvement in global health. Objectives: To determine the total fat and salt content of milk bread products, and to analyze the compliance of the salt content with the recommendation of the Portuguese Integrated Strategy for the Promotion of Healthy Eating (EIPAS). Methodology: During 2020, 12 sweet bread products were acquired from the major stores in Portugal. Then, total fat content (acid hydrolysis followed by Soxhlet extraction with petroleum ether) and salt content (Charpentier-Volhard titration method) were determined. Main findings: Total fat content varied between 5.0 and 21.3 g/100 g with an average of 12.6 g/100 g. Regarding the salt content and according to EIPAS, it is intended to achieve a content lower than 0.3 g/100 g. In this study 91.7% of the sweet bread products have a salt content higher than 0.3 g/100 g. The average was 0.78 g/100 g and the lowest salt content was 0.29 g/100 g. Conclusion: Sweet bread products have high salt and fat contents, thus evidencing the importance of defining strategies for reformulating these products in order to obtain a gradual and effective reduction in the levels of these nutrients, and contribute to promoting public health.